DOP081 Genital granulomatosis in Crohn's disease: results of the ECCO CONFER study. (16th January 2018) - Dederichs, F; Iesalnieks, I; Sladek, M; Tzivinikos, C; Hansen, R; Muñoz, C; Pavli, P; Cavicchi, M; Abitbol, V; Rahier, J -F; Vavricka, S; Katsanos, K; et al.
Abstract: Background: Genital granulomatosis (GG) is a extraintestinal form of Crohn's disease (CD), characterised by granulomatous inflammation of the genital skin without contact to the gastrointestinal tract. Little is known about GG as most publications are case reports or small series, and only sporadic in male cases. Methods: Cases of GG were retrospectively collected through the Collaborative Network For Exceptionally Rare case reports project of the European Crohn′s and Colitis Organization. The aims of this study were to extensively describe GG in patients with CD, with particular attention to male cases and to provide data on the response to treatments in GG. Results: Forty patients (9 males, 31 females) were diagnosed having GG in 21 centres, mostly as oedema and/or ulcers (95%). Histological confirmation of granulomas was obtained in 70% of the cases. CD location was colonic or ileocolonic in 97% and perianal disease was documented in 57%. There was no significant difference between males and females in CD phenotype and genital lesions. GG was the first manifestation of IBD in one third of the patients; these patients were younger at the time of GG occurrence and they all were non-smokers. GG occurred in the absence of gastrointestinal disease activity in 30% of the cases. After median follow-up period of 30 months (range, 9 to 154 months), clinical response to applied treatment was documented in all but one patient. In case of monotherapy as first-line treatment attempt 91% of the patients responded to systemic corticosteroid treatment, 56% of the patients responded to immunomodulators, and 81% of the patients responded to anti-TNFα agents. The best long-term response was observed on anti-TNFα therapy in 46% of the cases. Conclusions: GG is a rare extraintestinal manifestation of CD, which can precede intestinal CD. It more frequently occurs in women, predominantly in the setting of colonic involvement of CD and perianal disease is often associated. Most cases are successfully managed with systemic corticosteroids or anti-TNFα agents.